The Yacht Tourism and the Competition of Common-Pool Resource in Phang-Nga Bay (in Thai) - Pandam, Pichet (Asia Social Issues, 2013)
This thesis is interested in yacht tourism which enormously expanded in Phang-Nga Bay and the responses from local communities. The study has been focused on the competition, the accession and usage of Common - Pool resources, as well as the process, the over-all impacts and the responses of the local villagers who affected by yacht tourism. The study found out that yacht tourism has invasively occupied local resources whereas the villagers use as their communal areas for fishery in many aspects, i.e. construction of marina, activity of continuing business of yacht marina and tourism. By these results, the local fisher-folks were gradually losing access to their fishing grounds and other related resources. Sometimes, even their fishing gears had been destroyed by yachts. Even it obviously caused many negative impacts on local communities, but yacht tourism has been supported by the government, the state authorities and local administration organizations since it could enhance local economy growth. Meanwhile there are many loop-holes in legal system related to yacht tourism business that the project investors can take more advantage with the support from all parties mentioned above.In response to the Common-Pool resources competition affected by yacht tourism, the affected villagers try to react in their own ways. However yacht tourism has its special characteristics that could initiate complex inter-actions within local communities; i.e. yacht tourism business can bring the huge economic benefits to local communities and most of yacht tourist groups tend to be the people with ecological concerns. Therefore, the owners of yacht tourism business tried not to blow up any social conflicts with local communities in order to keep their good images. By this reason, the villagers could get more opportunity to negotiate with yacht tourism business. From this study, the reaction of the local people responded to yacht tourism business is not only their total objection. In case, when they learned that the objection is quite impossible, the negotiation to limit an expansion of affected areas in their communities will be prioritized while the most important aspect is the negotiation floor is how to make benefit sharing among different groups of villagers. การท่องเที่ยวเรือยอชท์กับการแย่งชิง ทรัพยากรส่วนรวมในอ่าวพังงา วิทยานิพนธ์ฉบับนี้สนใจว่า การท่อง เที่ยวเรือยอชท์ที่ขยายตัวอย่างมากในอ่าวพังงา ได้แย่งชิงทรัพยากรส่วนรวมอะไรไปจากการเข้า ถึงและใช้ประโยชน์ของชาวบ้านมีกระบวนการ อย่างไร ผลกระทบที่เกิดขึ้นต่อชาวบ้านเป็น อย่างไร ชาวบ้านตอบสนองต่อการเข้ามาแย่ง ชิงทรัพยากรดังกล่าวอย่างไร ผลการศึกษาพบ ว่าการท่องเที่ยวเรือยอชท์ได้เข้ามาแย่งชิง ทรัพยากรส่วนรวมที่ชาวบ้านใช้ในการทาประมง ในหลายลักษณะจากการสร้างท่าเรือยอชท์ การดำเนินธุรกิจต่อเนื่องจากท่าเรือ และการดำเนินกิจกรรมการท่องเที่ยว การแย่งชิงทรัพยากรดังกล่าวทำให้ชาวบ้านเข้าถึงทรัพยากรประมงและทรัพยากรอื่นที่ต้องพึ่งพาในการ ทำประมงได้น้อยลงและบางครั้งเครื่องมือถูกทำลายโดยเรือยอชท์ด้วย แต่ที่การท่องเที่ยวเรือยอชท์สามารถดำเนินการได้ทั้งที่สร้างผลกระทบ ต่อชาวบ้านอย่างมาก เพราะได้รับการสนับสนุนจากรัฐบาล จากทาง ราชการ และจากองค์การบริหารส่วนท้องถิ่น เนื่องจากเป็นธุรกิจที่จะ ก่อให้เกิดความเติบโตทางเศรษฐกิจอย่างมาก ในขณะเดียวกันก็มี ช่องว่างทางกฎหมายให้เจ้าของโครงการฉกฉวยไปสร้างประโยชน์ได้ โดยการสนับสนุนของผู้เกี่ยวข้อง อย่างไรก็ตามชาวบ้านที่ได้รับ ผลกระทบก็พยายามที่จะเคลื่อนไหว เพื่อตอบสนองต่อการเข้ามา แย่งชิงทรัพยากรดังกล่าว แต่ว่าการท่องเที่ยวเรือยอชท์ก็มีลักษณะ เฉพาะที่ทำให้การตอบสนองของชาวบ้านมีความซับซ้อน กล่าวคือ การท่องเที่ยวเรือยอชท์มีผลประโยชน์ที่จะเกิดขึ้นแก่คนในท้องถิ่น อย่างมาก และกลุ่มคนที่เรียกว่านักท่องเที่ยวเรือยอชท์เป็นกลุ่มคนที่มี ความคิดไปในแนวที่เห็นความสำคัญของสิ่งแวดล้อม ธุรกิจเกี่ยวกับ ท่องเที่ยวเรือยอชท์จึงพยายามไม่ให้เรื่องราวของตนกลายเป็นประเด็น ทางสังคม ความต้องการที่จะสร้างภาพลักษณ์ดังกล่าวจึงช่วยเปิด พื้นที่ให้ชาวบ้านต่อรองได้มาก ดังนั้นชาวบ้านจึงไม่ได้ตอบสนองแบบ คัดค้านอย่างสุดขั้ว แต่เมื่อคัดค้านการเกิดขึ้นไม่สำเร็จก็มุ่งไปที่การ ต่อรองเพื่อจะกัดเขตการขยายตัวและการเกิดผลกระทบ และที่สำคัญ คือการแบ่งปันผลประโยชน์จากการท่องเที่ยวเรือยอชท์ โดยชาวบ้านที่ ต่อรองนี้จะมีหลายกลุ่มแตกต่างกันไป